Ultra-High-Frequency Ultrasound in the Evaluation of Paediatric Pilomatricoma Based on the Histopathologic Classification - Li, Li; Xu, Jiaosheng; Wang, Siwei; Yang, Jun (Frontiers in Medicine, 2021)
Background: Pilomatricoma (PM) is one of the most common benign tumors in children. However, the inaccuracy of preoperative diagnosis and evaluation is high. Noninvasive examinations including dermoscopy and ultrasound are helpful for diagnosing and evaluating PM. To date, ultra-high-frequency ultrasonographic features of PM have been rarely studied. Objective: We aimed to investigate the ultra-high frequency ultrasonographic features of PM in a large pediatric cohort and to determine the associations of these features with the clinical features of different histological subtypes of PM. Methods: Patients who had both preoperative ultra-high-frequency ultrasonographic evaluation and pathological diagnosis of PM were enrolled. A series of infantile hemangiomas and cutaneous cysts during the same period were included as controls. Histological findings, including the stage, calcifying type, and ultrasonographic features of each lesion, were described. Results: A total of 133 patients with PM were included, and 147 PM lesions were analyzed. The male-to-female ratio was 1:1.58, and the median age of onset was 91 (range: 10-188) months. On ultra-high-frequency ultrasonography, PM presented as heterogeneous (144/147, 98.0%), well-demarcated (143/147, 97.3%), and hypoechoic (126/147, 85.7%) tumors located between the deep dermis and subcutaneous tissue (139/147, 94.6%). The most common features were internal echogenic foci (135/147, 91.8%), hypoechoic rim (133/147, 90.5%), posterior acoustic shadowing (94/147, 63.9%). Fourteen (9.5%) lesions were histologically categorized in the early stage, 58 (39.5%) in the fully developed stage, 65 (44.2%) in the early regressive stage and 10 (6.8%) in the late regressive stage. Three calcifying types, including scattered dots, clumps and arcs, were observed on histology, which corresponded well with grey-scale imaging on ultra-high-frequency ultrasonography. Each calcifying type was significant different in various histological stages (P=0.000), among which scattered dots were mainly present in the early and fully developed stage and arc-shaped calcifying were present in the regressive stages. Conclusions: PM is a heterogeneous, well-demarcated, hypoechoic tumor located between the deep dermis and the subcutis on ultra-high-frequency ultrasonography. The most common features are internal echogenic foci (calcifying) and hypoechoic rim. Calcifying types can help in the staging of PM. Ultra-high-frequency ultrasound is a useful tool for the diagnosis and evaluation of PM.